Filtration rates in inorganic filters submitted to different repose periods - Teixeira, Denis Leocádio; Matos, Antonio Teixeira De; Monaco, Paola Alfonsa Vieira Lo; Eustáquio Júnior, Valdeir; Baker, Sandy Athaíde Archer (Acta Scientiarum. Agronomy, 2012)
This work aimed to evaluate the filtration rate in organic filters after being subjected to different repose periods in the primary treatment of swine wastewater (SWW). Filtration columns were mounted in PVC pipes measuring 100 mm in diameter and 600 mm in length and filled with 2-5 mm sawdust particles. Five different repose periods were evaluated: 1, 2, 4, 8 and 16 days after the first filtration, carrying out three batches. The SWW filtration rate decreased with the operating time of the filters, which can be attributed to clogging of pores resulting from high concentrations of suspended solids (SS) present in this type of wastewater. In the three batches, it was observed that the repose periods of 1, 2 and 4 days were not sufficient to unclog the pores, however, repose periods of 8 and 16 days for the filter medium resulted in increases of the filtration rate, only 59 and 72% of the initial rate, respectively.

Com a realização deste trabalho, objetivou-se avaliar a taxa de filtração em filtros orgânicos, após terem sido submetidos a diferentes tempos de pousio, no tratamento primário da água residuária da suinocultura. Colunas de filtragem foram montadas em tubos de PVC de 100 mm de diâmetro e 600 mm de comprimento, tendo sido preenchidas com serragem de madeira, na granulometria de 2-5 mm. Foram avaliados cinco diferentes períodos de pousio: 1; 2; 4; 8 e 16 dias após efetuada a primeira filtração, realizando-se 3 bateladas. A taxa de filtração da ARS decresceu com o tempo de operação dos filtros, o que pode ser atribuído à obstrução dos poros decorrente das elevadas concentrações de sólidos suspensos (SS) presentes neste tipo de água residuária. Nas três bateladas, observou-se que os períodos de pousio de 1; 2 e 4 dias não foram suficientes para desobstrução dos poros, no entanto, períodos de pousio de 8 e 16 dias do material filtrante, proporcionaram aumento na taxa de filtração do material, ainda que tenha sido recuperado, respectivamente, apenas 59 e 72% da taxa inicial.
Keywords: Solids removal; Wastewater treatment; Repose period